Multiphase reinforced high-toughness high-conductivity TiB2-based composite material and in-situ preparation method thereof

Through the in-situ reaction sintering process, the mixing of different Ti sources and particle sizes and sintering additives are used to generate high-density, high-toughness, and high-conductivity TiB2-based composite materials, which solves the fracture toughness and conductivity of existing TiB2 ceramic materials. Inadequate problems and improve sintering performance.

CN119241251AActive Publication Date: 2025-01-03JIANGSU UNIV

Patent Information

Application Number
CN202411382937.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The fracture toughness and conductivity of existing TiB2 ceramic materials are insufficient, and when a variety of reinforcement phases are introduced, there are problems of reinforcement contamination and density reduction in the sintering process.

Method used

In situ reaction sintering process is adopted, through the mixing of different Ti sources, B4C powder and TiB2 powder of different particle sizes, combined with rotary stirring of sintering aid and ultrasonic oscillation, followed by ball mill mixing and screening granulation, and finally oscillation under vacuum conditions Hot pressing or discharge plasma sintering generates fine TiCx and elongated TiB grains, forming a conductive network to improve the density and toughness of the material.

Benefits of technology

A high-density, high-toughness, and high-conductivity TiB2-based composite material is realized, with a fracture toughness greater than 7.2MPa·m1/2 and a resistivity less than 6.5μΩ·cm, reducing enhanced body pollution and improving sintering performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241251A_ABST
    Figure CN119241251A_ABST
Patent Text Reader

Abstract

The invention provides a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material and an in-situ preparation method thereof, and belongs to the field of TiB2 composite materials. The preparation method comprises the following steps: selecting a Ti source, B4C powder and TiB2 powder with different particle sizes as raw materials, firstly mixing a sintering aid, then adding the aid into a TiB2 matrix, carrying out ball-milling mixing and screening granulation, and carrying out oscillation hot pressing or spark plasma sintering under a vacuum condition to obtain the multiphase reinforced TiB2-based composite material. According to the preparation method, an in-situ reaction sintering process is adopted, and a competitive reaction in a system is regulated and controlled, so that the metallurgical-grade combined high-toughness and high-conductivity TiB2-based composite material which takes a TiB2 matrix as a framework and multiple reinforced phases (TiCx, TiB, C and the like) as fillers is constructed. Meanwhile, the cost of the raw materials is low, the preparation process is simple, and the optimization of the components, the structure and the performance of the TiB2-based composite material can be realized only by regulating and controlling the component proportion of the raw materials, so that the application requirements in the extreme environment fields such as aluminum electrolysis cathode materials, high-temperature engine materials and aerospace materials can be better met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of TiB2 composite materials, and in particular relates to a multiphase reinforced TiB2-based composite material and an in-situ preparation method thereof. Background Art

[0002] Titanium diboride (TiB2), as a kind of ultra-high temperature ceramic, has many ideal properties such as high strength, high hardness, good corrosion resistance, excellent high temperature and chemical stability. This makes it an ideal material for extreme environment applications, such as cutting tools, bulletproof armor, high temperature engines and cathode materials. However, the overall covalent interaction of TiB2 ceramics is strong and the atomic self-diffusion coefficient is small, which poses a huge challenge to the improvement of fracture toughness.

[0003] In order to improve the fracture toughness of TiB2 ceramic materials, the fracture toughness of TiB2 ceramic materials can be improved by introducing a reinforcing phase that is thermodynamically compatible with TiB2, has a similar crystal structure, and can strengthen the matrix. For example, carbides have good electrical conductivity, excellent oxidation resistance, and high-temperature plasticity, which can improve the toughness and densification of composite materials; the unique physical and chemical properties and crystal structure of monoborides can be combined with matrix toughening; carbon has excellent reducibility and electrical conductivity, which can remove the oxide layer on the surface of the composite material and enhance the electrical conductivity.

[0004] However, the introduction of a single reinforcement phase does not improve the performance of TiB2-based composite materials. In the prior art, the fracture toughness of the composite material obtained by the method of preparing TiB2-TiC composite ceramics by reacting Ti powder with B4C powder needs to be improved; the extraction of TiB grains in the TiB2-TiB composite material prepared by SPS sintering will improve the mechanical properties, but will increase the pores inside the ceramic and reduce the density; although the TiB2-C composite ceramic prepared by hot pressing sintering has a lower resistivity, the addition of C reduces the density to 92%, and the fracture toughness is only 1.5MPa·m 1 / 2 In addition, during the ceramic sintering process, as the types of reinforcement phases introduced increase, problems such as reinforcement contamination and wettability between ceramic particles and the matrix caused by the mechanical mixing process will become more and more serious, which will seriously affect the densification and sintering properties of TiB2-based composites.

[0005] Therefore, how to improve the sintering process, reduce the contamination of the reinforcement while introducing multiple reinforcement phases, improve the wettability between the reinforcement phase and the matrix, and improve the densification, mechanical and electrical properties of the composite material, and prepare multiphase reinforced high-toughness and high-conductivity TiB2-based composite materials through in-situ reaction sintering, is the key and difficulty that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of pure phase TiB2, such as difficulty in densification, low fracture toughness and poor conductivity, the present invention proposes a method for preparing a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material through an in-situ reaction sintering process. Different Ti sources, B4C powders and TiB2 powders with different particle sizes are used as sintering raw materials. The sintering aids are mixed by rotating stirring combined with ultrasonic oscillation, and then the aids are added to the TiB2 matrix for ball milling mixing and screening granulation. The oscillation hot pressing or discharge plasma sintering is performed under vacuum conditions, so that the fine TiCx (the vacant TiCx generated by the in-situ reaction will show differences with the change of the C atom content in the system, 0.2≤x≤1) grains generated by the in-situ reaction can fill the lattice gaps and limit the grain growth of the TiB2 matrix. The slender TiB grain pull-out structure can achieve the strengthening of the TiB2 matrix. The conductive network established by the precipitated free carbon can effectively reduce the resistivity of the composite material. The clean matrix-reinforcement interface can make TiB2, TiCx, TiB and C more closely combined. In this way, a TiB2-based composite material with high density, high toughness and high conductivity is obtained.

[0007] In order to solve the problems existing in the existing sintering technology, the specific technical solution adopted by the present invention is as follows:

[0008] An in-situ preparation method of a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material comprises the following steps:

[0009] Step 1, Ti source, B4C powder, and type A TiB2 powder are mixed at a molar ratio of Ti:B4C:TiB2 of 3:1:α, solvent I is added, mixed by rotary stirring and ultrasonic vibration, and then rotary evaporated to obtain a sintering aid, wherein 0<α≤0.2;

[0010] The sintering aid and the B-type TiB2 powder are mixed in a molar ratio of B4C in the sintering aid: TiB2 in the B-type TiB2 powder of 1:β to obtain a powder, and a ball milling medium and a solvent II are added to the powder for ball milling and mixing, vacuum drying, and sieving to obtain a mixed powder; wherein 0<β≤0.5, and the mass ratio of powder: ball milling medium: solvent II is 1:(1-8):1;

[0011] Step 2, adding a binder to the mixed powder to combine the powder, sieving through a sieve, and vacuum drying to obtain a granulated powder;

[0012] Step 3, placing the granulated powder in a mold, and performing oscillation hot pressing sintering or spark plasma sintering under vacuum conditions to obtain a multi-phase reinforced high-toughness and high-conductivity TiB2-based composite material.

[0013] Furthermore, in step 1, the Ti source includes one or a mixture of two or more of titanium powder, titanium sponge, and titanium hydride; the D50 of the Ti source is 5 to 30 μm, and the purity is greater than 99.9%; the D50 of the B4C powder is 0.5 to 5 μm, and the purity is greater than 99.5%; the purity of Class A TiB2 powder is greater than 98.5%, and the purity of Class B TiB2 powder is greater than 98%.

[0014] Furthermore, in step 1, 0.1≤α≤0.2; 0.2≤β≤0.5.

[0015] Furthermore, in the step 1, the type A TiB2 powder selected as the sintering aid has a finer particle size, D50 of 0.5 to 1.5 μm; the type B TiB2 powder selected as the matrix has a coarser particle size, D50 of 5 to 7 μm.

[0016] Furthermore, in step 1, the solvent I is one or more of anhydrous ethanol, acetone, and ethyl acetate; the rotary stirring speed of the sintering aid is 150-300 rpm, the ultrasonic oscillation frequency is 70-120 Hz, and the mixing time of the rotary stirring and ultrasonic oscillation is 3-5 hours; the rotary evaporation temperature is 85-95°C; the ball milling medium is zirconia ball milling beads, and the solvent II is one or more of anhydrous ethanol, acetone, ethyl acetate or tetrahydrofuran; the ball milling speed of the ball milling mixing is 400-800 rpm, and the ball milling time is 3-7 hours; the vacuum drying temperature is 90-110°C, and the drying time is 2-6 hours.

[0017] Furthermore, in the step 1, the mass ratio of the powder: the ball milling medium: the solvent II is 1: (2-6): 1;

[0018] Furthermore, in step 2, the binder is a mixture of two or more of anhydrous ethanol, hydroxymethyl cellulose, polyethylene, polypropylene, and paraffin, and the added amount is 0.05wt% to 0.45wt%.

[0019] Furthermore, in step 2, the mesh size of the sieve is 70 to 120 meshes; the vacuum drying temperature is 80 to 120° C., and the drying time is 2 to 7 hours.

[0020] Furthermore, in step 3, the oscillation hot pressing sintering parameters are: first, the temperature is increased from room temperature to 900-1300°C at a heating rate of 5-30°C / min, the amplitude pressure is (20-35)±5MPa, and the temperature is kept for 20-40min; then, the temperature is increased to 1600-2000°C at a heating rate of 15-30°C / min, the amplitude pressure is (40-50)±5MPa, and the temperature is kept for 60-120min;

[0021] Spark plasma sintering parameters: first, heat the temperature from room temperature to 620-850°C at a heating rate of 200-300°C / min, keep warm for 1-3min, and the sintering pressure is 10-15MPa; then heat the temperature to 900-1300°C at a heating rate of 100-200°C / min, keep warm for 3-5min, and the sintering pressure is 20-30MPa; then heat the temperature to 1500-1900°C at a heating rate of 100-200°C / min, the sintering pressure is 30-40MPa, and the holding time is 3-15min.

[0022] The multiphase reinforced high-toughness and high-conductivity TiB2-based composite material prepared by the in-situ preparation method is a multiphase reinforced TiB2-based composite material containing TiCx, TiB, and C, and its fracture toughness is greater than 7.2MPa·m 1 / 2 , resistivity is less than 6.5μΩ·cm.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The present invention adopts a two-step mixing process. In the first step, the sintering aid Ti source, B4C and fine-grained Class A TiB2 are preferentially mixed evenly to form a core-shell Ti@(B4C+TiB2) coating structure. Since the Ti source is in good contact with B4C and fine-grained Class A TiB2, the occurrence of in-situ reactions and competitive reactions in the sintering neck promotion system can be effectively reduced. In the second step, coarse-grained Class B TiB2 is added and mixed. Due to the addition of coarse-grained Class B TiB2, the TiB2 generated by the in-situ reaction of the Ti source and B4C nucleates and grows, promoting the occurrence of the reaction, and at the same time constructing a metallurgical-grade TiB2-based composite material with a TiB2 matrix as a skeleton and various fine reinforcing phases as fillers.

[0025] 2. The vacuum oscillation hot pressing sintering technology adopted in the present invention can not only promote the plastic deformation ability of the TiB2 matrix through oscillation pressure under the condition of amplitude pressure (20-50) ± 5MPa, but also help to reduce the diffusion distance between grains, reduce the porosity of the composite material, and promote the densification of TiB2-based composite materials; the vacuum discharge plasma sintering has a fast heating rate (100-300℃ / min), and can achieve ceramic densification in a relatively short time (2-15min). The spontaneous reaction in the in-situ sintering technology makes it possible to achieve in-situ generation of multiple reinforcing phases and densification of composite materials at a relatively low sintering temperature (1500-1900℃).

[0026] 3. The present invention adopts multi-stage vacuum oscillation hot pressing and discharge plasma sintering technology, wherein the oscillation pressurization in the first stage of oscillation hot pressing (900-1300°C) can effectively promote the occurrence of in-situ and competitive reactions in the system; the second stage (1600-2000°C) oscillation pressurization removes pores and reduces the intercrystalline spacing. A close bond between the TiB2 matrix and the reinforcement phase is achieved. The first stage of discharge plasma (620-850°C) promotes the decomposition of the Ti source (TiH2) and the removal of gas, thereby improving the densification of the composite material; the second stage (900-1300°C) uses pulse current to achieve rapid in-situ and competitive reactions in the system at low temperature; the third stage (1500-1900°C) quickly achieves the densification and toughening bond between the TiB2 matrix and the reinforcement phase.

[0027] 4. The present invention can simply and quickly obtain multiphase reinforced TiB2-based composite materials such as titanium boride (TiB2), titanium carbide (TiCx), titanium monoboride (TiB), free carbon (C), etc. through in-situ competitive reactions, which not only reduces the pollution of the reinforcement, but also improves the wettability, compatibility and uniformity between the reinforcement phase and the matrix, while reducing the sintering driving force; and the fine TiCx grains generated in situ can fill the lattice gaps and limit the grain growth of the TiB2 matrix, the grain extraction structure of the slender TiB can achieve the strengthening and toughening of the TiB2 matrix, and the precipitated C can promote the establishment of a conductive network, thereby obtaining a high-density, high-toughness, and high-conductivity TiB2-based composite material. By regulating the competitive reaction in the system, the fracture toughness of the TiB2-based composite material is greater than 7.2MPa·m 1 / 2 , resistivity is less than 6.5μΩ·cm.

[0028] Ti+TiB2=2TiB

[0029] 3Ti+B4C=2TiB2+TiC

[0030] TiC+2TiB+B4C=3TiB2+2C

[0031] 3Ti+B4C+(α+β)TiB2=(α+β+3 / 2)TiB2+1 / 2TiC+TiB+1 / 2C (0<α+β≤0.7) BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 SEM images of the surface (a) and fracture cross-section (b) of the TiB2-based composite material obtained in Example 1 of the present invention.

[0033] Figure 2 This is the EDS image of each phase in the TiB2-based composite material obtained in Example 1 of the present invention.

[0034] Figure 3This is the XRD diagram of the TiB2-based composite material obtained in Example 1 of the present invention.

[0035] Figure 4 SEM images of the surface (a) and fracture cross-section (b) of the TiB2-based composite material obtained in Example 2 of the present invention.

[0036] Figure 5 This is the XRD diagram of the TiB2-based composite material obtained in Example 2 of the present invention.

[0037] Figure 6 SEM images of the surface (a) and fracture cross-section (b) of the TiB2-based composite material obtained in Example 3 of the present invention.

[0038] Figure 7 This is the XRD diagram of the TiB2-based composite material obtained in Example 3 of the present invention.

[0039] Figure 8 The surface SEM image (a) and backscattered electron image (b) of the TiB2-TiC composite material obtained in Comparative Example 1 of the present invention.

[0040] Fig. 9 This is the XRD diagram of the TiB2-TiC composite material obtained in Comparative Example 1 of the present invention.

[0041] Among them, Ⅰ represents TiB2, Ⅱ represents TiC, Ⅲ represents C, and Ⅳ represents TiB. DETAILED DESCRIPTION

[0042] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the specific implementation modes of the present invention will be described in detail below with reference to the accompanying drawings.

[0043] Embodiment 1:

[0044] An in-situ preparation method of a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material comprises the following steps:

[0045] Step 1: Mix the ingredients

[0046] First, commercially available high-purity titanium sponge (D50 is 21 μm, purity greater than 99.9%), B4C powder (D50 is 1 μm, purity greater than 99.5%), and Class A TiB2 powder (D50 is 1.0 μm, purity greater than 98.5%) are prepared into a sintering aid at a molar ratio of Ti: B4C: TiB2 of 3:1:0.2; then, an appropriate amount of acetone is added, and the mixture is mixed uniformly by rotary stirring and ultrasonic oscillation, wherein the rotary stirring speed is 300 rpm, the ultrasonic oscillation frequency is 70 Hz, and the stirring and oscillation time is 3 hours; then, rotary evaporation is performed at 85°C;

[0047] Then, the sintering aid and the B-type TiB2 powder (D50 is 6 μm, purity is greater than 98%) are mixed at a molar ratio of B4C in the sintering aid: TiB2 in the B-type TiB2 powder of 1:0.2 to obtain a powder, and zirconium oxide ball milling beads and acetone are added to perform ball milling mixing; wherein the mass ratio of powder: ball milling medium: solvent is 1:2:1, the ball milling speed is 400 rpm, and the ball milling time is 7 hours;

[0048] Finally, the mixed powder was obtained after vacuum drying at 110 °C for 2 h.

[0049] Step 2, screening and granulation

[0050] Anhydrous ethanol and 0.05 wt % polyethylene were added as binders to the mixed powder obtained in step 1 to combine the powders, and the dried ball-milled powder was sieved and granulated through an 80-mesh sieve, and vacuum dried at 80° C. for 7 h to obtain granulated powder.

[0051] Step 3: In-situ sintering

[0052] According to the size diameter d = 20mm, 6g of the granulated powder obtained in step 2 was weighed, and the powder was placed in a graphite mold for vacuum reaction spark plasma sintering. The temperature was raised from room temperature to 620℃ at 300℃ / min, and the temperature was kept for 1min, and a pressure of 15MPa was applied; then the temperature was raised to 1300℃ at 200℃ / min, and a pressure of 30MPa was applied, and the temperature was kept for 3min; then the temperature was raised to 1700℃ at a heating rate of 200℃ / min, and a pressure of 30MPa was applied, and the temperature was kept for 15min before cooling to room temperature. The prepared multiphase reinforced TiB2-based composite material has a density of 98.5%, a Vickers hardness of 21.6GPa, and a fracture toughness of 7.8MPa·m 1 / 2 , resistivity 5.7μΩ·cm.

[0053] The surface and fracture cross-section SEM, EDS and XRD of the obtained TiB2-based composite material are shown in Figure 1 , 2As shown in Figure 3. Since Ti in the raw material will react with B4C to preferentially generate TiC, and Ti will also react with fine-grained Class A TiB2 in the raw material to generate TiB, the molar ratio between Ti and B4C is broken, resulting in a competitive reaction between Ti and (B4C and TiB2), and the unreacted B4C will continue to react with the in-situ generated TiCx to generate a more stable TiB2 phase and free carbon until the reaction is completed. From EDS and XRD, it can be seen that the dark gray phase is TiB2, the light gray phase is TiCx, the black phase is free C, and the elongated crystal is TiB. However, due to the fast heating rate and short holding time, the reaction between Ti and TiB2 in the sintering aid and between TiC and B4C generated in-situ by (Ti and B4C) is not complete, resulting in a low content of TiB and free C in the system, and a low improvement in fracture toughness and electrical conductivity.

[0054] Embodiment 2:

[0055] An in-situ preparation method of a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material comprises the following steps:

[0056] Step 1: Mix the ingredients

[0057] First, commercially available high-purity Ti powder (D50 is 10 μm, purity greater than 99.9%), B4C powder (D50 is 0.5 μm, purity greater than 99.5%), and Class A TiB2 powder (D50 is 0.5 μm, purity greater than 98.5%) are prepared into a sintering aid at a molar ratio of Ti: B4C: TiB2 of 3:1:0.15; then, an appropriate amount of anhydrous ethanol is added, and the mixture is evenly mixed by rotary stirring and ultrasonic oscillation, wherein the rotary stirring speed is 200 rpm, the ultrasonic oscillation frequency is 90 Hz, and the stirring and oscillation time is 4 hours; then, rotary evaporation is performed at 90°C;

[0058] Then, the sintering aid and the B-type TiB2 powder (D50 is 5 μm, purity is greater than 98%) are mixed in a molar ratio of B4C in the sintering aid: TiB2 in the B-type TiB2 powder of 1:0.4 to obtain a powder, and zirconium oxide ball milling beads and anhydrous ethanol are added for ball milling mixing; wherein the mass ratio of powder: ball milling medium: solvent is 1:4:1, the ball milling speed is 600 rpm, and the ball milling time is 5 hours;

[0059] Finally, the mixed powder was obtained after vacuum drying at 100 °C for 4 h.

[0060] Step 2, screening and granulation

[0061] Anhydrous ethanol and 0.25 wt % hydroxymethyl cellulose were added as binders to the mixed powder obtained in step 1 to bind the powder, and the dried ball-milled powder was sieved and granulated through a 100-mesh sieve, and vacuum dried at 100° C. for 5 h to obtain granulated powder.

[0062] Step 3: In-situ sintering

[0063] According to the size diameter d = 20mm, weigh 6g of the granulated powder obtained in step 2, place the powder in a graphite mold, and perform vacuum oscillation hot pressing sintering. First, heat the temperature from room temperature to 1300℃ at a heating rate of 25℃ / min, with an amplitude pressure of 30±5MPa, and keep it warm for 30min; then heat the temperature to 1800℃ at a heating rate of 25℃ / min, with an amplitude pressure of 45±5MPa, and keep it warm for 60min before cooling to room temperature. The prepared multiphase reinforced TiB2-based composite material has a density of 99.4%, a Vickers hardness of 23.5GPa, and a fracture toughness of 8.6MPa·m 1 / 2 , resistivity 4.2μΩ·cm.

[0064] The surface and fracture cross-section SEM and XRD of the obtained TiB2-based composite material are shown in Figure 4 and 5 As shown. From SEM and XRD analysis, it can be seen that the main distribution of the composite material is still large-grained TiB2 and fine-grained TiC, with elongated TiB and free C distributed locally. Under the support of the dynamic pressure of oscillating hot pressing, the reaction activity between Ti in the sintering aid and fine-grained A-type TiB2 and B4C is higher, and the reaction between Ti and TiB2 and between TiC generated in situ (Ti and B4C) and raw material B4C is more intense, resulting in an increase in the content of TiB and free C, which significantly increases the fracture toughness of the composite material and significantly reduces the resistivity.

[0065] Embodiment 3:

[0066] An in-situ preparation method of a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material comprises the following steps:

[0067] Step 1: Mix the ingredients

[0068] First, commercially available sintering aid TiH2 (D50 is 25 μm, purity is greater than 99.9%), B4C powder (D50 is 4 μm, purity is greater than 99.5%), and Class A TiB2 powder (D50 is 1.5 μm, purity is greater than 98.5%) are prepared into a sintering aid at a molar ratio of Ti: B4C: TiB2 of 3:1:0.1; then add an appropriate amount of ethyl acetate, mix evenly by rotary stirring and ultrasonic oscillation, wherein the rotary stirring speed is 150 rpm, the ultrasonic oscillation frequency is 120 Hz, and the stirring and oscillation time is 3 hours; then rotary evaporation is performed at 95°C;

[0069] Then, the sintering aid and the B-type TiB2 powder (D50 is 7 μm, purity is greater than 98%) are combined according to the molar ratio of B4C in the sintering aid: TiB2 in the B-type TiB2 powder of 1:0.5, and zirconium oxide ball milling beads and ethyl acetate are added to carry out ball milling and mixing; wherein, the mass ratio of powder: ball milling medium: solvent is 1:7:1, the ball milling speed is 800 rpm, and the ball milling time is 3 hours;

[0070] Finally, the mixed powder was obtained after vacuum drying at 90 °C for 6 h.

[0071] Step 2, screening and granulation

[0072] Anhydrous ethanol and 0.45 wt % polypropylene were added as binders to the mixed powder obtained in step 1 to combine the powders, and the dried ball-milled powder was sieved and granulated through a 120-mesh sieve, and vacuum-dried at 120° C. for 3 h to obtain granulated powder.

[0073] Step 3: In-situ sintering

[0074] Weigh 6g of the granulated powder obtained in step 2 according to the size diameter d=20mm, place the powder in a graphite mold, and perform vacuum reaction spark plasma sintering, heating from room temperature to 850℃ at 300℃ / min, keeping the temperature for 3min, applying a pressure of 10MPa; then heating to 1300℃ at 100℃ / min, applying a pressure of 20MPa, keeping the temperature for 5min; then heating to 1900℃ at a heating rate of 100℃ / min, applying a pressure of 40MPa, keeping the temperature for 3min, and then cooling to room temperature. The prepared multiphase reinforced TiB2-based composite material has a density of 97.3%, a Vickers hardness of 19.4GPa, and a fracture toughness of 7.2MPa·m 1 / 2 , resistivity 6.5μΩ·cm.

[0075] The surface and fracture cross-section SEM and XRD of the obtained TiB2-based composite material are shown in Figure 6 and 7 As shown. Due to the reduction in the proportion of fine-grained A-type TiB2 in the sintering aid, the reaction between Ti and TiB2 is difficult to maintain; in addition, the crystal structure of the coarse-grained B-type TiB2 matrix is ​​relatively complete and has low reaction activity. As the proportion increases, it will hinder the competitive reaction between B4C and Ti and the generated TiC in the system, resulting in a further decrease in the content of TiB and free C. At the same time, due to the decomposition of TiH2, the H2 generated during the rapid sintering process is not removed in time, resulting in more pores on the surface of the composite material and a significant decrease in density. As a result, the fracture toughness and density of the composite material are reduced, and the resistivity increases.

[0076] Comparative Example 1:

[0077] An in-situ preparation method of a single-phase reinforced high-toughness and high-conductivity TiB2-based composite material specifically comprises the following steps:

[0078] Step 1: Mix the ingredients

[0079] Commercially available high-purity Ti powder (D50 is 10 μm, purity is greater than 99.9%) and B4C powder (D50 is 0.5 μm, purity is greater than 99.5%) are prepared into a sintering aid at a molar ratio of Ti:B4C of 3:1, and then an appropriate amount of anhydrous ethanol is added, and the mixture is mixed evenly by rotary stirring and ultrasonic oscillation, and then rotary evaporation is performed, wherein the rotary stirring speed is 200 rpm, the ultrasonic oscillation frequency is 90 Hz, the stirring oscillation time is 4 h, and the rotary evaporation temperature is 90°C;

[0080] Then, the sintering aid and the TiB2 matrix (D50 is 5 μm, purity is greater than 98%) are combined according to the molar ratio of B4C in the sintering aid: TiB2 in the TiB2 matrix of 1:0.4, and zirconium oxide ball milling beads and anhydrous ethanol are added to perform ball milling and mixing; wherein the mass ratio of powder: ball milling medium: solvent is 1:4:1, the ball milling speed is 600 rpm, and the ball milling time is 5 hours;

[0081] Finally, the mixed powder was obtained after vacuum drying at 100 °C for 4 h.

[0082] Step 2, screening and granulation

[0083] Anhydrous ethanol and 0.25 wt % hydroxymethyl cellulose were added as binders to the mixed powder obtained in step 1 to bind the powder, and the dried ball-milled powder was sieved and granulated through a 100-mesh sieve, and vacuum dried at 100° C. for 5 h to obtain granulated powder.

[0084] Step 3: In-situ sintering

[0085] According to the size diameter d = 20mm, weigh 6g of the granulated powder obtained in step 3, place the powder in a graphite mold, and perform vacuum oscillation hot pressing sintering. First, heat the temperature from room temperature to 1300℃ at a heating rate of 25℃ / min, with an amplitude pressure of 30±5MPa, and keep it warm for 30min; then heat the temperature to 1800℃ at a heating rate of 25℃ / min, with an amplitude pressure of 45±5MPa, and keep it warm for 60min before cooling to room temperature. The density of the prepared TiB2-TiC composite material is 95.2%, the Vickers hardness is 17.8GPa, and the fracture toughness is 5.2MPa·m 1 / 2 , resistivity 13.4μΩ·cm. The surface SEM, backscattered electron and XRD of the obtained TiB2-based composite material are shown as follows Figure 8 and 9 shown.

[0086] Table 1 Comparison of sintering aids, sintering methods and composite material properties of Examples 1 to 3 and Comparative Example 1

[0087] project Example 1 Example 2 Example 3 Comparative Example 1 Sintering Aids <![CDATA[3Ti-B4C-0.2TiB2]]> <![CDATA[3Ti-B4C-0.15TiB2]]> <![CDATA[3Ti-B4C-0.1TiB2]]> <![CDATA[3Ti-B4C]]> Raw material ratio 1:0.2 1:0.4 1:0.5 1:0.4 Sintering method Discharge plasma Oscillating heat pressing Discharge plasma Oscillating heat pressing Relative density 98.5% 99.4% 97.3% 95.2% Vickers hardness 21.6GPa 23.5GPa 19.4GPa 17.8GPa Fracture toughness <![CDATA[7.8MPa·m 1 / 2 ]]> <![CDATA[8.6MPa·m 1 / 2 ]]> <![CDATA[7.2MPa·m 1 / 2 ]]> <![CDATA[5.2MPa·m 1 / 2 <!-- 6 -->]]> Resistivity 5.7μΩ·cm 4.2μΩ·cm 6.5μΩ·cm 13.4μΩ·cm

[0088] As shown in Table 1, by changing the sintering aid and sintering method, the density, mechanical properties and electrical properties of TiB2-based composites can be greatly improved by using in-situ reaction sintering and competitive reaction behavior. Compared with Ti-B4C two-phase additive addition and single-phase reinforced TiB2-TiC composites, the multi-phase reinforced TiB2-based composites prepared by adding Ti-B4C-TiB2 three-phase raw materials combined with a two-step mixing process have comprehensively improved densification, fracture toughness and conductivity.

[0089] In summary, the in-situ reaction sintering process can construct a high-toughness and high-conductivity TiB2-based composite material with a TiB2 matrix as the skeleton and TiCx, TiB, C and other reinforcing phases as fillers by regulating the progress of the competitive reaction in the system.

[0090] The above-described embodiments are all preferred implementations of the present invention, and do not limit the present invention in other forms. Any technician familiar with the profession may use the above content to make changes or follow suit. However, any changes made to the above embodiments based on the essence of the method of the present invention without departing from the content of the scheme in the present invention still fall within the scope of protection of the present invention.

Claims

1. An in-situ preparation method of a multiphase reinforced high-toughness and high-conductivity TiB2-based composite material, characterized in that: The following steps are involved: Step 1, Ti source, B4C powder, and type A TiB2 powder are mixed at a molar ratio of Ti:B4C:TiB2 of 3:1:α, solvent I is added, mixed by rotary stirring and ultrasonic vibration, and then rotary evaporated to obtain a sintering aid, wherein 0<α≤0.2; The sintering aid and the B-type TiB2 powder are mixed in a molar ratio of B4C in the sintering aid: TiB2 in the B-type TiB2 powder of 1:β to obtain a powder, and a ball milling medium and a solvent II are added to the powder for ball milling and mixing, vacuum drying, and sieving to obtain a mixed powder; wherein 0<β≤0.5, and the mass ratio of powder: ball milling medium: solvent II is 1:(1-8):1; Step 2, adding a binder to the mixed powder to combine the powder, sieving through a sieve, and vacuum drying to obtain a granulated powder; Step 3, placing the granulated powder in a mold, and performing oscillation hot pressing sintering or spark plasma sintering under vacuum conditions to obtain a multi-phase reinforced high-toughness and high-conductivity TiB2-based composite material.

2. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1 is characterized in that: In step 1, 0.1≤α≤0.2; 0.2≤β≤0.

5.

3. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1 is characterized in that: In step 1, the D50 of type A TiB2 powder is 0.5-1.5 μm; the D50 of type B TiB2 powder is 5-7 μm.

4. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1 is characterized in that: The Ti source in step 1 includes one or a mixture of two or more of titanium powder, titanium sponge, and titanium hydride; the D50 of the Ti source is 5-30μm, and the purity is greater than 99.9%; the D50 of the B4C powder is 0.5-5μm, and the purity is greater than 99.5%; the purity of Class A TiB2 powder is greater than 98.5%, and the purity of Class B TiB2 powder is greater than 98%.

5. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1 is characterized in that: In the step 1, the solvent I is one or more of anhydrous ethanol, acetone, and ethyl acetate; the rotation stirring speed of the sintering aid is 150-300 rpm, the ultrasonic oscillation frequency is 70-120 Hz, and the mixing time of the rotation stirring and ultrasonic oscillation is 3-5 hours; the rotary evaporation temperature is 85-95°C; the ball milling medium is zirconia ball milling beads, and the solvent II is one or more of anhydrous ethanol, acetone, ethyl acetate or tetrahydrofuran; the ball milling speed of the ball milling mixing is 400-800 rpm, and the ball milling time is 3-7 hours; the vacuum drying temperature is 90-110°C, and the drying time is 2-6 hours.

6. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1 is characterized in that: In the step 1, the mass ratio of the powder: the ball milling medium: the solvent II is 1: (2-6):

1.

7. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1 is characterized in that: In the step 2, the binder is a mixture of two or more of anhydrous ethanol, hydroxymethyl cellulose, polyethylene, polypropylene, and paraffin, and the added amount is 0.05wt% to 0.45wt%.

8. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1, characterized in that: In the step 2, the mesh size of the sieve is 70 to 120 meshes; the vacuum drying temperature is 80 to 120° C., and the drying time is 2 to 7 hours.

9. The in-situ preparation method of the multiphase reinforced high-toughness and high-conductivity TiB2-based composite material according to claim 1, characterized in that: The oscillation hot pressing sintering parameters in step 3 are: first, heating from room temperature to 900-1300°C at a heating rate of 5-30°C / min, with an amplitude pressure of (20-35)±5MPa, and keeping warm for 20-40min; then heating to 1600-2000°C at a heating rate of 15-30°C / min, with an amplitude pressure of (40-50)±5MPa, and keeping warm for 60-120min; The spark plasma sintering parameters are as follows: firstly, heating from room temperature to 620-850°C at a heating rate of 200-300°C / min, keeping the temperature for 1-3min, and the sintering pressure is 10-15MPa; then heating to 900-1300°C at a heating rate of 100-200°C / min, keeping the temperature for 3-5min, and the sintering pressure is 20-30MPa; then heating to 1500-1900°C at a heating rate of 100-200°C / min, the sintering pressure is 30-40MPa, and the keeping time is 3-15min.

10. A multiphase reinforced high-toughness and high-conductivity TiB2-based composite material prepared by the in-situ preparation method according to any one of claims 1 to 9, characterized in that: The composite material is a TiB2-based composite material containing TiCx, TiB, and C multiphase reinforcement, and its fracture toughness is greater than 7.2MPa·m 1 / 2 , resistivity is less than 6.5μΩ·cm.

Citation Information

Patent Citations

  • Method for promoting sintering of titanium boride ceramic by using reaction aids

    CN102249697A

  • High-temperature-resistance Ti (C, N)-TiB2-HEAs composite metal ceramic material and preparation method thereof

    CN109504886A

  • Titanium diboride-boron carbide-titanium carbide composite ceramic material and hot-pressing preparation method thereof

    CN114315367A

  • TiB2-based armored composite ceramic material

    CN114605156A

  • Titanium boride-titanium carbide-carbon composite ceramic material capable of generating titanium carbide in situ and preparation method of titanium boride-titanium carbide-carbon composite ceramic material

    CN115677367A

Cited By

  • High-toughness and high-conductivity TiB2-TiC-C1 / 2D composite ceramic and preparation method thereof

    CN121426578A